Características de composição química e atividades da Peroxidase e da Polifenoloxidase dos cultivares de abacaxi MD-2 e Pérola - Silva, Vânia Maria Barboza da (2012)
Pineapple is a fruit widely appreciated as fresh fruit. But its chemical composition varies widely between different cultivars. This study evaluated the content of some chemical components and the activity of peroxidase and polyphenoloxidase in pineapple MD-2 and Pearl mature, comparing them with each other. The chemical components of two cultivars analyzed showed that, statistically, the Soluble Solids and Titratable Total Acidity showed higher values than MD-2 pineapple pineapples in Pearl, possibly explaining the latter being more appreciated as fresh fruit by locals while the MD-2 pineapples are more accepted for export. The optimum pH and temperature for the peroxidase activity of MD-2 pineapples were pH 5.0 at 40 ° C and less favorable pH found in this study form. In pineapples Pearl optimal conditions recorded were 50 ° C and pH 5.5 and less favorable 40 º C and pH 6.0. At 30 ° C the specific activity was recorded 3.69 and 3.92 U mg protein-1 for pineapples and Pearl MD-2, respectively. The natural pH of 3.23 MD-2 and 3.59 pH of Pearl were statistically different between the cultivars did not differ tannins and content of L-ascorbic acid was significantly higher in Pearl pineapples. However, the peroxidase activity was significantly higher in Pearl, that the MD-2 and therefore the MD-2 deterioradora less subject to the action of this enzyme.